Β-Blockers versus calcium channel blockers for acute rate control of atrial fibrillation with rapid ventricular response: a systematic review. (June 2015) - Martindale, Jennifer L.; deSouza, Ian S.; Silverberg, Mark; Freedman, Joseph; Sinert, Richard
Abstract : This is a systematic review of the literature to compare the efficacy of calcium channel blockers to β-blockers for acute rate control of atrial fibrillation with rapid ventricular response in the emergency department setting. PubMed, EMBASE, and the Cochrane Registry were searched. Relative risk (95% confidence interval) was calculated between drugs and methodological quality of included studies was evaluated. Of the 1003 studies yielded by our initial search, two met inclusion criteria and provided sufficient data. These were randomized double-blinded studies ( n =92) comparing intravenous diltiazem with intravenous metoprolol. The combined relative risk of acute rate control by diltiazem versus metoprolol was 1.8 (95% confidence interval 1.2–2.6). On the basis of the paucity of available evidence, diltiazem may be more effective than metoprolol in achieving rapid rate control, but high-quality randomized studies are needed. Abstract : Supplemental Digital Content is available in the text.